Personalizing information retrieval using task features, topic knowledge, and task product - Liu, Jingjing (International ACM SIGIR Conference on Research and Development in Information Retrieval, 2009)
Keywords: dept.ils

A comparison of public library use of statistics – a cross‐country survey report - Liu, Yan Quan (New Library World, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilizing statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight differences and similarities of the uses the two countries’ directors make of statistics and the statistical information that directors find particular useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
Keywords: China; Librarians; Libraries; Management; Statistics; USA; dept.ils

Where does professional education on digital libraries lead our new librarians - Liu, Yan Quan (Springer Verlag, 2003)
This study investigates the state of school education for digital libraries. For this study, a web survey was conducted of syllabi of courses on the subject of digital libraries. Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a "hands-on" element, a practical component of the course that requires that the students interact with digital libraries. Those students who have received practical experience with digital libraries, like those provided in the "hands-on" courses, are best served for future practice in the field of librarianship. © Springer-Verlag Berlin Heidelberg 2003.
Keywords: Digital libraries; E-learning; Education; Practical experience; Professional education; School education; Students; Teaching; Web surveys; dept.ils

Is the education on digital libraries adequate - Liu, Yan Quan (New Library World, 2004)
This study investigates the state of education for digital libraries. For this study, a Web survey was conducted of syllabi of courses on the subject of digital libraries (DL). Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a “hands-on” element, a practical component of the course that requires that the students interact with digital libraries. Not all of the course contents are up-to-date in the field of library and information technology. While the quality of DL education seems to have advanced at those schools and institutions that offer classes with “hands-on” requirements, the educational approach at many of the “hands-off” universities seems somewhat technophobic and overly dependent on outdated pedagogical methods. Those students who have received practical experience with digital libraries, like those provided in the “hands-on” courses, appear to be best served for future practice in the field of librarianship. © 2004, Emerald Group Publishing Limited
Keywords: Digital libraries; Europe; Libararies; Library facilities; North America; Surveys; dept.ils

Best practices, standards and techniques for digitizing library materials: a snapshot of library digitization practices in the USA - Liu, Yan Quan (Online Information Review, 2004)
This study investigates current practice in digitizing library materials in the USA. Building a good digital collection has been a common task, pervasive in all types of libraries. Digitization becomes more and more crucial, affecting libraries while they work towards becoming digital. Researchers and practitioners would like to know what practices have been developed to deal with the challenges that pose the most significant problems or concerns for libraries in digitization. Through probing some widespread issues on what materials to digitize, and the associated standards and technologies in digitization in US libraries, this survey of current literature reveals a number of prominent library digitization practices, methods and challenges, and highlights the best practices, trends and interests in library digitization pertaining to both policy and technology marketplace issues.
Keywords: Analog to digital conversion; Data processing; Digital libraries; Document image processing; Electronic media; Information and Library Science; Multimedia systems; Project management; Public policy; Societies and institutions; Standards; Technical problems; United States of America; dept.ils

The use of statistics in the managerial process by public library directors in China and the USA: a cross‐country survey - Liu, Yan Quan (Library Management, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilising statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight the differences and similarities between the ways in which the two groups of directors make use of statistics, and the statistical information that directors find particularly useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process, and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
Keywords: China; Libraries; Management; Public Libraries; Statistics; USA; dept.ils

Digital Libraries, Its Theory and Practices. - Liu, Yan Quan (2009)
Thirteen chapters and 47 sections of the book"Digital libraries, its theory and practices" were worked on and the book is ready to send to the publisher. Did a paper that was accepted by the journal Library Hi Tech. Visited China and gave 2 seminars in 2 universities in China.
Keywords: dept.ils; faculty_collection; sabbatical_report

Enhancing digital information access in public libraries - Ayers, Kathleen; Liu, Yan Quan (2007)
Purpose To explore the impact of public digital library resources on urban residents, to elucidate the current usage patterns of public digital library resources/services and levels of satisfaction with the resources/content in urban digital libraries and make recommendations as to steps that would improve service to this population. Design/Methodology/Approach We conducted an anonymous user-completed survey study of 6 urban libraries to collect demographic and information regarding satisfaction with Digital Library (DL) resource and patterns of use. Findings Our respondents represented a cross section of races, genders, ages, and educational backgrounds. Our results in this much-needed area of study demonstrate that libraries should plan to provide more access, less filtering, regular upgrades, and more training to use the resources. Practical Limitations/Implications Larger studies should be used to follow up this report, in order to be able to obtain a generalized understanding of overall patterns of urban residents using DLs in public settings. Recruitment techniques did not adequately sample potential (but not current) DL users. Originality/Value This study contributes to a scant empirical data set addressing the impact that access to public digital information and services have on urban residents. We offer new data and recommendations that will guide public library administrators in enhancing the impact, efficiency and value of public DL resources/services to improve the digital learning environment for life-long educaiton at all levels in a broad community of urban users.
Keywords: dept.ils; ⛔ No DOI found

The impact of digital resource and service use on urban residents in new england public Libraries—A survey report - Liu, Yan Quan; Wnuk, Agnes (Public Library Quarterly, 2009)
Today, access to digital information is essential to patrons using public libraries, whether they have contact with computers at home, work or school or whether the public library is their only contact. In order to evaluate and ultimately enhance public library digital resources and services, it is critical for administrators, librarians and digital information architects to recognize the impact their current digital offerings have on users. This study utilizes a survey to gauge the perceptions of patrons who use digital resources and services in six urban New England public libraries as part of ongoing research into digital information access in public libraries in the United States from the perspective of users.
Keywords: Digital divide; Digital libraries; Digital resources; Digital resources services; New England public libraries; Public libraries; Urban libraries; dept.ils; peer-reviewed

Developing an integrated public library service in Dongguan, one of China's fastest growing cities - Liu, Yan Quan; Li, Donglai (New Library World, 2007)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved in the development of an urban library service system in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the development of an integrated public service system and its distribution of information among libraries and information centers in an urban community. Findings - Constructing an integrated public service system is an important trend in urban libraries in the new millennium. Drawing from the Dongguan library's integrated public service system that aims to master better various resources from whole service area, this text summarizes technology innovation and the significant results of the Dongguan library system redevelopment, providing an absorbing insight into developments in the Chinese public library service. Originality/value - While the ultimate goal of integration is to provide better services to meet the information-seeking needs of urban residents, it is necessary to meet these needs through a technological breakthrough in the administration of clustered libraries, to instill a central branch system, and to work out the advantages of group service.
Keywords: China; Digital libraries; Library management Public sector organizations; Public libraries; dept.ils

The present and future of China's National Science and Technology Library - A new paradigm of sci-tech information resource sharing - Meng, Liansheng; Liu, Yan Quan (New Library World, 2005)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved with the development of the National Science and Technology Library (NSTL) in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the historical development of scientific and technological information sharing among libraries and information centers and issues around construction of the NSTL. Findings - Since the establishment of its network service system at the end of 2000, the NSTL has made rapid progress in constructing a sci-tech information resource sharing system and offering web-based information services to the patrons of scientific and technical communities all over China. Originality/value - This paper is the first exploration that brings to the forefront the foundational background of the NSTL, the characteristics of its organizational structure, the functions of its service, and the tentative plan to increase its accessibility and usability. Symptomatic of the function of the NSTL constructing pattern will hopefully shed light not only to the reformation of the Chinese sci-tech information management system, but also to the development of scientific digital libraries in the world. © Emerald Group Publishing Limited.
Keywords: China; Digital libraries; Document management; Information services; National libraries; Worldwide web; dept.ils

International and Comparative Studies in Information and Library Science: A Focus on the United States and Asian Countries - Liu, Yan Quan; Cheng, Xiaojun (Libraries and librarianship--an international perspective ; no. 3, 2008)
Keywords: Asia; Asia; Information science; Comparative librarianship; International librarianship; Library science; United States; Information science; United States; Library science; dept.ils; faculty_collection

The use of national public library statistics by public library directors - Liu, Yan Quan; Zweizig, Douglas L (The Library Quarterly, 2001)
Keywords: dept.ils; ⛔ No DOI found

Digital information access in urban/suburban communities: A survey report of public digital library use by the residents in Connecticut - Liu, Yan Quan; Martin, Craig; Roehl, Eileen; Yi, Zhixian; Ward, Sheila (OCLC Systems and Services, 2006)
Purpose - The purpose of this paper is to explore the impact of public digital services on urban/suburban residents, to uncover the current usage of public digital services and levels of satisfaction with the digital resources/content in urban digital libraries (networked computers with specific information infrastructure designed free for public use). Design/methodology/approach - A qualitative approach is used as a main stream in the research framework as the method of inquiry. Qualitative one-to-one interviews include surveying users who use public library websites, observing the users, consulting librarians about the users, and interviewing the users. Findings - Provides demographic patterns of the patron's interaction with the digital services public libraries provide, and the satisfaction and compliances the residents have regarding information access through the digital technology in urban/suburban Connecticut. Practical implications - Because of the small number of participants, this study has limitations in being generalized to an understanding of overall patterns of urban residents using digital resources in public settings in the USA or elsewhere, however, it could be a good pilot study for a nation-wide survey with the methods tested. Originality/value - This study helps fulfill the scant empirical attention given to the impact access to public digital information or use of digital library services on the urban/suburban residents, offers new data that help public library administrators enhance the impact, efficiency and value of the public digital library services to improve the digital learning environments for life-long education at all levels in a broad community of urban-suburban users. © Emerald Group Publishing Limited.
Keywords: Design/methodology/approach; Digital learning environment; Digital libraries; Digital technologies; Information retrieval; Information services; Information studies; Life-long educations; Public libraries; Public library; Qualitative approach; Specific information; Surveys; dept.ils

Preparation, microstructure and physical characteristics of ferroelectric pb 5 ge 3 O 11 thin films for memory application - Liu, Y. X.; Caragianis-Broadbridge, Christine; Lehman, A. H.; McGuinness, J. K.; Ma, Tso-Ping (2003)
We report sol-gel process of Pb5Ge3O11 (PGO) as well as the microstructure and physical properties of ferroelectric PGO films for memory applications. The PGO sol was prepared from lead acetate hydrate, germanium isopropoxide, and di(ethylene glycol) ethyl ether. The reactions taking place during the sol-gel process were examined in detail, Diethanolamine (DEA) was added to help maintain the desired species ratio and prevent germanium oxide precipitation. The preferred orientation of the PGO thin films was well controlled by the heating and reflux procedures in the sol-gel preparation process. Additionally, to examine the impact of post-deposition processing, selected samples were oxygen annealed at temperatures ranging from 450-650°C. The samples were characterized with X-ray diffraction (XRD), non-contact (planview) atomic force microscopy (NC-AFM). The resulting data indicate that the microstructure and physical properties of PGO films depend strongly on the precursor preparation as well as the post deposition annealing temperature.
Keywords: Atomic force microscopy; Ferroelectric materials; Glove boxes; Isopropoxide; Lead compounds; Low-power memory; MISFET devices; Microstructure; Sol-gels; Thermal effects; Thin films; X ray diffraction; dept.ils